2008
DOI: 10.1002/biot.200700208
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and free radical scavenging activities of an exopolysaccharide from a probiotic bacterium

Abstract: Probiotic bacteria synthesize extracellular polysaccharides (EPSs) with commercially significant physiological and therapeutic activities. This important class of biomolecules is also characterized by their ability to remove reactive oxygen species (ROS) that are formed in the intestine by various metabolic reactions; hence, they exhibit antioxidant activities. Our probiotic bacterium, Bacillus coagulans RK-02, produces an EPS during the exponential and stationary growth phases when grown in a glucose mineral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(97 citation statements)
references
References 32 publications
(34 reference statements)
3
86
0
3
Order By: Relevance
“…Previous experimental studies showed that Bacillus coagulans was able to regulate cell factors, enhanced the phagocytosis of phagocytic cells, enhanced the activity of NK, T and B cells, and increased the expression of IgA, IgG and IgM (Kodali et al, 2008). Consistently, the results of the present experiment showed that Bacillus coagulans can enhance the immune function of the gut of yellow-feathered broilers.…”
Section: Bacillus Coagulans Enhance the Immune Function Of The Intestsupporting
confidence: 91%
“…Previous experimental studies showed that Bacillus coagulans was able to regulate cell factors, enhanced the phagocytosis of phagocytic cells, enhanced the activity of NK, T and B cells, and increased the expression of IgA, IgG and IgM (Kodali et al, 2008). Consistently, the results of the present experiment showed that Bacillus coagulans can enhance the immune function of the gut of yellow-feathered broilers.…”
Section: Bacillus Coagulans Enhance the Immune Function Of The Intestsupporting
confidence: 91%
“…Zhang et al [22] showed that the sulfated polysaccharide fraction from Porphyra haltanesis, an important alga in China, has antioxidant activity, and a strong scavenging effect for superoxide radical and it inhibits lipid peroxidation. In another study, Kodali & Sen [23] reported that the polysaccharide isolated from probiotic bacteria had antioxidant and free radical scavenging activities. It has also been found that consumption of complex carbohydrates in combination with different antioxidant micronutrients may enhance the antioxidant defenses and improve lipid metabolism [1].…”
Section: Carbohydrate Contentmentioning
confidence: 99%
“…Antioxidant properties of EPS have been also described by Kodali et al They have demonstrated that EPS from Bacillus coagulans RK-02 has antioxidant properties and may act as a scavenger of free radicals. These properties were comparable with those of standard antioxidants such as vitamin C and E [22]. Further, we investigated the influence of EPS 37 on the phagocytic function of macrophages.…”
Section: Discussionmentioning
confidence: 73%